2014
DOI: 10.1111/nmo.12378
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the human fecal microbiota and depression

Abstract: The Oscillibacter type strain has valeric acid as its main metabolic end product, a homolog of neurotransmitter GABA, while Alistipes has previously been shown to be associated with induced stress in mice. In conclusion, the taxonomic correlations detected here may therefore correspond to mechanistic models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
547
7
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 873 publications
(639 citation statements)
references
References 32 publications
31
547
7
18
Order By: Relevance
“…A negative correlation was observed between Faecalibacterium and the severity of depressive symptoms. In another investigation several correlations between microbial composition and depression were reported in a study of 37 depressed patients and 18 healthy controls (Naseribafrouei et al, 2014). The order Bacteroidales was over-represented.…”
Section: Microbiota Immunity and Depressionmentioning
confidence: 98%
“…A negative correlation was observed between Faecalibacterium and the severity of depressive symptoms. In another investigation several correlations between microbial composition and depression were reported in a study of 37 depressed patients and 18 healthy controls (Naseribafrouei et al, 2014). The order Bacteroidales was over-represented.…”
Section: Microbiota Immunity and Depressionmentioning
confidence: 98%
“…In one study on human subjects with depression, no significant difference in the composition of gut microbiota was found between depressed patients and a control group. 109 However, another recent study examined the composition of fecal microbiota in 46 patients with depression and 30 healthy controls, and reported significant differences with increased population of Bacteroidetes, Proteobacteria, and Actinobacteria, and decreased population of Frimicutes in patients with depression. 110 Other evidence that might suggest a role for gut microbiota in the pathogenesis of depression is from studies that have shown certain probiotics can alleviate depressive symptoms in rodent models.…”
Section: Gut Microbiota and Depressionmentioning
confidence: 99%
“…The gut microbiota also regulates brain function and behavior through microbiota-gut-brain axis. Many diseases have been found to be related with the number and composition of gut microbiota, including obesity (Ley et al, 2006), diabetes (Qin et al, 2012), hypertension (Yang et al, 2015), liver cirrhosis (Qin et al, 2014), autism (Finegold et al, 2010), depression (Naseribafrouei et al, 2014), Parkinson's disease (Scheperjans et al, 2015), and so on. However, the research on AD and gut microbiota is just beginning.…”
Section: Introductionmentioning
confidence: 99%